Analisis Pengaruh Overinvestment terhadap Kinerja Perusahaan dengan Kebijakan Hutang dan Kebijakan Dividen sebagai Variabel Moderasi - Qadri, Lailatul; Nurhalis, Nurhalis (Syiah Kuala University Press, 2024)
This research aims to analyze the effect of overinvestment on firm performance with dividend policy and debt policy as moderating variables in trading, service and investment companies listed on the Indonesian stock exchange. This testing was carried out for five years, namely the 2017-2021 period. The sample selection technique uses a purposive sampling method. This research uses quantitative methods. The type of data used in this research is secondary data, namely quantitative data which includes investment, debt, dividend and firm performance data which is proxied by Return on Assets (ROA) in trading, service and investment companies listed on the Indonesia Stock Exchange. The data collection technique used is panel data. Research analysis uses Moderated Regression Analysis. Overinvestment is calculated using the residual of the new investment equation. The results of this research show that overinvestment has a negative and significant influence on firm performance. Moderation of dividends and debt can change the direction of the negative influence that overinvestment has on firm performance so as to reduce agency conflicts that occur in the company.